The Ukrainian context of Comenius studies: philosophical, pedagogical, psychological aspects - Kobernyk, Alexander; Osadchenko, Inna; Tkachuk, Larysa (Siedleckie Zeszyty Komeniologiczne seria Pedagogika, 2019)
The article describes philosophical, pedagogical and psychological aspects of Comeni-us’s scientific ideas based on the analysis of scientific findings of Ukrainian authors in different historical times. It is found that the works of the prominent educator began to be analyzed in detail by Ukrainian scholars in the second half of the 19th century. The article also thematically chronologizes studies on the work of John Amos Comenius: pedagogical ideas; biographical data; the role of ideas in the context of developing sciences of different fields, such as philosophy, history, pedagogy. The article shows that the philosophical aspect of Ukrainian Comeniology is characterized by the focus of scholars of the 19th century on Comenius’s theological ideas and, through their prism, on the functioning of the Ukrainian education system; the exemplarity of his figure in overcoming obstacles to Ukraine’s independence; the analysis of his ideas from the beginning of Ukraine’s independence through a nationally updated context of socio-cultural relations; the quintessence of the philosophical concept of “eternal peace”. The philosophical aspect of Ukrainian Comeniology is substantially connected with the pedagogical aspect: the everyday relevance of Comenius’s pedagogical ideas in all the analyzed historical periods of Comenius studies (from the middle of the 19th century up to the present day); the eloquence of the educator’s ideas, in particular the deterministic historical and social conditions of the teach-er’s professionalization and the image of the modern pupil; the permanent relevance of Comeni-us’s pedagogical principles (democracy, cultural conformity through national identity); ideas for schools teaching in national languages, etc. The psychological aspect of Ukrainian Сomeniology has not yet been revealed. Considerable attention has been paid to the psychological ideas of John Amos Comenius through the compilation of the quotations corresponding to the psycholog-ical concept of today.